Corynebacterium urinapleomorphum sp. nov., a new bacterial species isolated from human urine sample. (September 2019) - Niang, E.H.A.; Lo, C.I.; Morand, A.; Ndongo, S.; Raoult, D.; Fournier, P.-E.; Fenollar, F.
Abstract: Corynebacterium urinapleomorphum sp. nov. stain Marseille-P2799 T (= CSURP2799; = DSM103272) is a new species from the order Corynebacteriales that was isolated from urine of a 2-month-old child with gastroenteritis.